Pengelolaan Bank Sampah Induk Berseri di Kecamatan Lubuk Pakam - Rita Ulina Br Ginting; Fikarwin Zuska; Irfan Simatupang (PERSPEKTIF, 2022)
This study aims to analyze best practices related to the ability of the Induk Berseri Waste Bank to maintain a relatively high income compared to other waste banks which generally have low incomes and its role in maintaining relationships with partners so that they are productive and in maintaining trust. This study uses a descriptive research method with a qualitative approach in the sense that the research is focused on the selected phenomena and wants to be understood in depth by using interview techniques. The results of this study are the presence of the Berseri Main Waste Bank in Lubuk Pakam District has encouraged smart city efforts, by inviting community cooperation to seek economic assistance for each partnered citizen. Creating awareness and knowledge as well as the ability to encourage participation in maintaining a clean environment. Some of the public opinions of the Berseri Parent Waste Bank are positive opinions with the helpful response to the Berseri Parent Waste Bank, while the obstacles that are still felt by residents who partner with the Berseri Parent Waste Bank are the frequent delays or delays in taking waste to residents and the prices are still low. The Main Trash Bank Berseri itself in its business really maintains a cooperative relationship with its partners and maintains trust so that it has a good image in the community.